Respuesta :
[tex]11-\dfrac{1}{2}y=3+6x\ \ \ \ \ |subtract\ 11\ from\ both\ sides\\\\-\dfrac{1}{2}y=-8+6x\ \ \ \ \ |change\ signs\\\\\dfrac{1}{2}y=8-6x\ \ \ \ \ |multiply\ both\ sides\ by\ 2\\\\y=4-3x[/tex]
Answer:
The value of the provided equation for y is [tex]y=-12x+16[/tex].
Step-by-step explanation:
Consider the provided equation.
[tex]11-\frac{1}{2}y=3+6x[/tex]
We need to solve the above equation for y.
Subtract 11 from both the sides.
[tex]11-11-\frac{1}{2}y=3-11+6x[/tex]
[tex]-\frac{1}{2}y=6x-8[/tex]
Multiply both the sides by -2
[tex]-\frac{1}{2}y\times -2=-2(6x-8)[/tex]
[tex]y=-12x+16[/tex]
Hence, the value of the provided equation for y is [tex]y=-12x+16[/tex].